Motivasi Dan Strategi Penguatan Petani Kopi Rakyat Dalam Pengolahan Produk Primer Dan Sekunder Di Wilayah Klaster Industri - Hesti Herminingsih; - Sudarko (Jurnal Ilmiah Inovasi, 2017)
AbstractIn Bondowoso Regency,coffee agribusiness development must be full supported with postharvest sectors for primer (green coffee) and second products (roasted bean coffee, ground coffee, instant coffee, etc.).  Aims of the research were 1) to analyze variations innovation and technology  of farmers postharvest sector for primer and second products, 2) to calculat level motivation  of smallholders coffee farmers farmers at postharvest sector for primer products, 3) to calculat level motivation  of smallholders coffee farmers at postharvest sector for second products 4) to formulate some strategy alternative to development groups of smallholders coffee farmers.The research has been conducted from  August to October 2013. It used descriptif quantitative methods. The research used was a survey using 30 respondents from and 10  informants from all of center smallholders coffee farmers and stakeholders  in Industry clusters Area  Bondowoso  Regency. Data analysis by descriptif, likert scale and Fields Factors analysis (FFA)The result showed that; 1) variations innovation and technology  of farmers postharvest sector for primer and second products is good category. 2) level motivation  of smallholders coffee farmers at postharvest sector for primer products were high level, 3) level motivation and ability of smallholders coffee farmers at postharvest sector for second  products were average level, 4) the strategy alternative to development smallholders coffee farmers with optimalisation and introduction coffee roaster and grider for group farmer scale in agribusiness development perspectives Keywords:  Coffee bean, motivation, Empowerment Strategyes, smallholders coffee farmers.